Doing Business in the East African Community 2013 : Smarter Regulation for Small and Medium-Size Enterprises - World Bank; International Finance Corporation (Washington, DC: World Bank Group, 2013)
Doing Business in the East African Community (EAC) 2013 is the fourth in a series of regional reports drawing on the global Doing Business project and its database. In recent years the Doing Business project has helped put business regulatory reform on the agenda of many countries-at all income levels. Over the past 8 years the 5 members of the EAC-Burundi, Kenya, Rwanda, Tanzania, and Uganda-have continued to take steps to make it easier for local firms to start up and operate. Continual improvement of the business environment is important for countries seeking to benefit from greater trade and investment through regional integration. The common market protocol, which entered into force in July 2010, is supposed to be fully implemented by December 2015. By that time the EAC is expected to have achieved the 'four freedoms'-free movement of people, goods, services and capital within the common market. Among the main tasks of the committees is to set up and implement coherent, broad-based regional reform programs to improve the investment climate of the region as a whole and make it an attractive destination for external investors. The Doing Business methodology is also responsive to the needs of policy makers. Rules and regulations are under the direct control of policy makers-and policy makers intending to change the experience and behavior of businesses will often start by changing rules and regulations that affect them. Doing Business captures several important dimensions of the regulatory environment as they apply to local firms. It provides quantitative measures of regulations for starting a business, dealing with construction permits, getting electricity, registering property, getting credit, protecting investors, paying taxes, trading across borders, enforcing contracts and resolving insolvency. The Doing Business data are based on domestic laws and regulations as well as administrative requirements. The data cover 185 economies-including small economies and some of the poorest economies, for which little or no data are available in other data sets.